BUDAYA BERBAGI PENGETAHUAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA: Kasus Gerakan Free Software dan Dounjinshi Culture - Ambar Sari Dewi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
From year to year, Indonesia’s position in the list of Human Development Index declined. One of them is because the quality of education. This resulted in low human qualities. Though today’s technology, opportunities to enhance the capabilities and qualityare wide open. Dounjinshi free software movement and culture are examples of cases used in this paper to explain how to improve the quality of human resources through knowledge sharing culture.